Exploring the Way Culture Shapes the Enactment of TPACK in Indonesian EFL Classrooms - Arriyani, Nurfisi; Hartono, Rudi; Fitriati, Sri Wuli; Pratama, Hendi (Yayasan Keluarga Guru Mandiri, 2026)
In the rapidly evolving landscape of digital education, understanding how cultural values influence technology integration is essential. This study investigates how Indonesian EFL lecturers make pedagogical decisions and enact the Technological Pedagogical Content Knowledge (TPACK) framework in culturally grounded ways. Drawing on both quantitative and qualitative data, the research involved a questionnaire distributed to 59 lecturers and in-depth interviews with 13 participants from various regions and institutions in Indonesia. The findings reveal that lecturers’ selection of digital tools and instructional strategies are mediated by beliefs about teacher authority, student respect, classroom order, and cultural appropriateness. While some lecturers, particularly older ones, favored structured, teacher-led digital practices, younger lecturers were more open to integrating interactive tools, though still within cultural boundaries. Rather than adopting global pedagogical models wholesale, participants actively adapted them to fit local expectations. The study concludes that TPACK is not a culturally neutral framework but is redefined by educators in context. This research contributes to the growing body of knowledge on culturally responsive digital pedagogy and highlights the importance of integrating sociocultural awareness into teacher-training and technology-adoption frameworks.